2010
DOI: 10.3310/hta14170
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol and selective and non-selective non-steroidal anti-inflammatory drugs (NSAIDs) for the reduction of morphine-related side effects after major surgery: a systematic review

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
75
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(89 citation statements)
references
References 9 publications
5
75
1
8
Order By: Relevance
“…The use of long-acting opioids for post-surgical pain has been demonstrated to be associated with increased health care utilization and costs 4 . Prior research in multiple surgical areas including orthopedics, obstetrics, and general surgery suggests that multimodal pain management including IV acetaminophen (IV APAP) for acute post-surgical pain improves patient outcomes and reduces hospital resource use [5][6][7][8][9] . Acetaminophen is a common component of multimodal pain management that may include both pharmaceutical and medical treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The use of long-acting opioids for post-surgical pain has been demonstrated to be associated with increased health care utilization and costs 4 . Prior research in multiple surgical areas including orthopedics, obstetrics, and general surgery suggests that multimodal pain management including IV acetaminophen (IV APAP) for acute post-surgical pain improves patient outcomes and reduces hospital resource use [5][6][7][8][9] . Acetaminophen is a common component of multimodal pain management that may include both pharmaceutical and medical treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have demonstrated a synergistic analgesic effect of opioid-NSAID combinations [1] [2] [3]. This synergistic effect is considered to be because of known different pharmacodynamic mechanisms of the two groups-opioids act via opioid receptors in the central nervous system and NSAIDs affect the synthesis of prostaglandins by inhibiting cyclooxygenase.…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs are commonly combinated with morphine following major surgery with the aim of reducing morphine's side-effects (McDaid et al, 2010). PCA has reduced the morbidity of cardiac, pulmonary, thromboembolic and renal diseases, and also reduced blood loss and transfusion requirements (Kehlet, 2004).…”
Section: Introductionmentioning
confidence: 99%